Community cervical cancer screening: barriers to successful home-based HPV self-sampling in Dabat district, North Gondar, Ethiopia: a qualitative study - Megersa, Bikila Soboka; Bussmann, Hermann; Bärnighausen, Till; Muche, Achenef Asmamaw; Alemu, Kassahun; Deckert, Andreas (PLOS ONE, 2020)
Objective To explore the barriers to successful home-based human papillomavirus (HPV) self-sampling in North Gondar, Ethiopia. Methods The study participants were women who had previously participated in a community-wide home-based HPV self-sampling pilot study, community health workers, women’s development army leaders, and the sample collectors of the home-based HPV self-sampling pilot study. A community based qualitative descriptive study was conducted. We applied purposive and convenience sampling. In total, 47 women participated in the study (in-depth interviews n = 22, four focus group discussions n = 25, 6-7 participants each). The study employed thematic analysis for clustering the emerged themes. Results Husband disapproval was identified as the main barrier to the acceptance of home-based HPV self-sampling. Social influence, lack of knowledge about cervical cancer and screening, lack of health education on cervical cancer and HPV-based screening, feeling healthy, and religious influence were identified as additional barriers. Fear of using Evalyn brush® for self-sampling was found to be the main barrier to the provision of a quality sample. The inability of the sample collectors to check the proper utilization of Evalyn brush® and the difficulty in understanding the instructions did also contribute to the low-quality. Providing health education concerning cervical cancer and HPV self-sapling to women, male involvement in the screening program, and linking the screening service to existing local health facilities were suggested to guarantee the success of home-based HPV self-sampling. Conclusions Educating women regarding cervical cancer and HPV testing, providing clear instructions on how to collect self-sample, and male involvement in the screening program are prerequisites for a successful implementation of home-based HPV testing. Women empowerment should also be focused to overcome the identified sociocultural barriers. Furthermore, the screening program should guarantee the timely provision of the test results and offering women follow-up examinations and treatment for abnormal findings.
Gesehen am 16.02.2022